Zoning and analysis of pervasive rainfall in rainy areas of Iran In the statistical period of 30 years (1987-1987) - Maryam saghafi; Gholamreza Barati; Bohloul Alijani; Mohammad Moradi (تحقیقات کاربردی علوم جغرافیایی)
Precipitation is a phenomenon resulting from complex atmospheric interactions and among climatic events, due to its vital role, it has special importance. The importance of precipitation durability, especially in arid and semi-arid regions, which includes most of Iran, is greater than its volume. The purpose of this study is to identify Iran's precipitation areas in terms of precipitation durability and its characteristics in each area. In order to investigate the durability of Iran's precipitation and to define a precipitation day as " a day with equal precipitation or greater than 0.5 mm", used from daily precipitation data of 80 synoptic stations of the country during the 6 cold months of the year from October to March in a period of 30 years (2016 - 1987). Setting data in daily tables in the first step, made possible to program in MATLAB environment to separate precipitation in ten groups from "one day" to "ten days" and in the second step in SPSS environment based on frequency characteristics, amount and precipitations average in the mentioned groups was done by the method of Ward merging and clustering. The process of the clustering on Iran's durability precipitation showed that there are seven almost homogeneous precipitation zones in Iran; the geographical arrangement of Iran's precipitation areas, reveals the dependence of Iran's precipitations amount on roughness, the path of precipitation systems, its proximity to humidity sources, and the effect of the sea. In terms of area’s location, it can be said that; the settlement of the four zones in the western half of Iran, despite its small size in front of the eastern half, is a reason for its heterogeneity.